الاستعارة بين الرماني وسيّد قطب في القرآن الكريم: دراسة مقارنة: The Metaphor between al-Rumani and Sayyid Qutb in the Holy Qur’an as a model: a comparative study - Syahadah, Fadhmah; Haji Daud, Nadwah (Universitas Darussalam Gontor, 2024)
This study, Metaphor between Al-Rumani and Sayyid Qutb in the Holy Qur'an: A Comparative Study, compared Sayyid Qutb, a well-known modern writer, with Al-Rumani, an older writer, in order to emphasize the metaphor technique. The study's approach will be twofold: first, it will define the terms